Wypisy źródłowe do biografi i polskich biskupów i opatów z czasów Rzeczypospolitej Obojga Narodów oraz niewoli narodowej doby zaborów (XVI-XIX w.)(Cz. X) - Prokop, Krzysztof R. (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The tenth part of the cycle for Source extracts for the biography of the Polish bishops and abbots from the time of the Polish-Lithuanian Commonwealth and the Partitions of Poland is entirely dedicated to the testimonies of the ordination of bishop representatives of the Old Polish Catholic episcopate at various times and circumstances. These testimonia consecrationis were taken from different categories of sources-primarily from (acta sacrarum functionum), from the books acta episcopalia, acta actorum capituli, records of informative process concerning bishoprics, from correspondence and diaries-only unpublished. These testimonies refer to the group of 195 hierarchs (including 11 of the Greek Catholic rite, 2 the Armenian Catholic Rite and the rest-the Latin rite), but when it comes to particular centuries these testimonies are presented as follows: 15th. – 4, 16th. – 7, 17th – 43, 18th – 91, 19th – 50. So far, there has been no information where and when a large number of bishops were consecrated, so the following work, presenting substantial portion of factual data acquired directly from archive material, contributes enormously to the state of research on this issue.